1989
DOI: 10.1017/s0950268800030478
|View full text |Cite
|
Sign up to set email alerts
|

High-level vancomycin-resistant enterococci causing hospital infections

Abstract: Nosocomial infection or colonization due to enterococci with high-level resistance to vancomycin (minimal inhibitory concentrations [MICs] between 64 and greater than 2000 mg/L) has occurred in 41 patients with renal disease. These vancomycin-resistant enterococci were cultured from many sources including blood. All but one strain contained one or more plasmids ranging in molecular weight from 1.0 to 40 Megadaltons (MDa). Vancomycin resistance was transferable by conjugation to a susceptible recipient strain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
191
1
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(200 citation statements)
references
References 27 publications
3
191
1
3
Order By: Relevance
“…Although Uttley et al 17 found that most resistant strains remained sensitive to other drugs such as ampicillin and ciprofloxacin, other reports had suggested the occurrence of multi-resistant organisms. The isolation of truly multiresistant organisms from two of our patients is a cause for concern.…”
Section: Discussionmentioning
confidence: 98%
“…Although Uttley et al 17 found that most resistant strains remained sensitive to other drugs such as ampicillin and ciprofloxacin, other reports had suggested the occurrence of multi-resistant organisms. The isolation of truly multiresistant organisms from two of our patients is a cause for concern.…”
Section: Discussionmentioning
confidence: 98%
“…6 " 11 In 1994, three more publications described outbreaks of VRE. 1214 These studies during the first 5 years of the VRE epidemic (1989)(1990)(1991)(1992)(1993)(1994) began to define the epidemiology of VRE colonization and infection and led to the following conclusions:…”
Section: Glen Mayhall MDmentioning
confidence: 99%
“…5 One of the first descriptions of vancomycin resistant enterococci (VRE) was in patients with end stage renal disease (ESRD) by Uttley et.al. 6 Risk factors for VRE colonization include host characteristics (immunosuppression, renal insufficiency and neutropenia), hospital factors (admission in an ICU or oncology ward) proximity to a VRE colonized patient, and extended duration of hospitalization and antimicrobial use. 7 VRE colonization independently increases a patient's risk of developing enterococcal infections, such as bloodstream infections (BSIs).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dialysis patients also have contributory underlying co-morbid conditions, frequent hospitalizations and antibiotic exposures which predispose them to colonization with VRE. 6 Since VRE colonization is a critical risk factor, the optimal method for preventing clinical infections is to prevent colonization. Once a patient becomes colonized with VRE, it is important to recognize modifiable risk factors that contribute to the development of infection in a colonized patient.…”
Section: Introductionmentioning
confidence: 99%